Global causes of maternal death: a WHO systematic analysis - Say, Lale; Chou, Doris; Gemmill, Alison; Tunçalp, Özge; Moller, Ann-Beth; Daniels, Jane; Gülmezoglu, A Metin; Temmerman, Marleen; Alkema, Leontine (The Lancet global health, 2014)
Data for the causes of maternal deaths are needed to inform policies to improve maternal health. We developed and analysed global, regional, and subregional estimates of the causes of maternal death during 2003–09, with a novel method, updating the previous WHO systematic review. We searched specialised and general bibliographic databases for articles published between between Jan 1, 2003, and Dec 31, 2012, for research data, with no language restrictions, and the WHO mortality database for vital registration data. On the basis of prespecified inclusion criteria, we analysed causes of maternal death from datasets. We aggregated country level estimates to report estimates of causes of death by Millennium Development Goal regions and worldwide, for main and subcauses of death categories with a Bayesian hierarchical model. We identified 23 eligible studies (published 2003–12). We included 417 datasets from 115 countries comprising 60 799 deaths in the analysis. About 73% (1 771 000 of 2 443 000) of all maternal deaths between 2003 and 2009 were due to direct obstetric causes and deaths due to indirect causes accounted for 27·5% (672 000, 95% UI 19·7–37·5) of all deaths. Haemorrhage accounted for 27·1% (661 000, 19·9–36·2), hypertensive disorders 14·0% (343 000, 11·1–17·4), and sepsis 10·7% (261 000, 5·9–18·6) of maternal deaths. The rest of deaths were due to abortion (7·9% [193 000], 4·7–13·2), embolism (3·2% [78 000], 1·8–5·5), and all other direct causes of death (9·6% [235 000], 6·5–14·3). Regional estimates varied substantially. Between 2003 and 2009, haemorrhage, hypertensive disorders, and sepsis were responsible for more than half of maternal deaths worldwide. More than a quarter of deaths were attributable to indirect causes. These analyses should inform the prioritisation of health policies, programmes, and funding to reduce maternal deaths at regional and global levels. Further efforts are needed to improve the availability and quality of data related to maternal mortality. USAID, the US Fund for UNICEF through a grant from the Bill & Melinda Gates Foundation to CHERG, and The UNDP/UNFPA/UNICEF/WHO/The World Bank Special Programme of Research, Development, and Research Training in Human Reproduction (HRP), Department of Reproductive Health and Research.